Asymmetric cryo-EM reconstruction of phage MS2 reveals genome structure in situ - Koning, Roman I (Nat Commun, 2016)
In single-stranded ribonucleic acid (RNA) viruses, virus capsid assembly and genome packaging are intertwined processes. Using cryo-electron microscopy and single particle analysis we determined the asymmetric virion structure of bacteriophage MS2, which includes 178 copies of the coat protein, a single copy of the A-protein and the RNA genome. This reveals that in situ, the viral RNA genome can adopt a defined conformation. The RNA forms a branched network of stem-loops that almost all allocate near the capsid inner surface, while predominantly binding to coat protein dimers that are located in one-half of the capsid. This suggests that genomic RNA is highly involved in genome packaging and virion assembly.